Child Grooming dalam Drama Koi No Tsuki - Ningtyas, Hamidah Harnum Ayu; Budiana, I Made; Aryani, Made Ratna Dian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study is entitled "Child Grooming in the Drama Koi No Tsuki". This study aims to determine the factors causing child grooming in the drama Koi No Tsuki which are analyzed using the hierarchy of needs theory by Abraham Maslow, and to determine the impact of child grooming victims in the drama Koi No Tsuki which is analyzed through the psychological impact approach on children or adolescents who are victims of sexual abuse. This study focuses on the analysis of the actions and behavior of the perpetrators and victims of child grooming in the context of the drama narrative. Qualitative descriptive methods are used in this study to provide an in-depth and detailed description of child grooming and to understand the characteristics, context, and implications of child grooming in the drama Koi No Tsuki. The data source used in this study is a Japanese drama entitled Koi No Tsuki which has 12 episodes with a duration of 24 minutes per episode. The results of the analysis show that Wako Taira’s basic needs for sex, job stability and stability of romantic relationships with her boyfriend, love, recognition from herself and from others are not met, so that Wako Taira seeks alternatives by exploiting vulnerable minors who can be dominated as compensation for the conditions she experiences. As a result of the child grooming, emotionally, Yumeaki Iko experiences shock, fear, depression, tantrums, and is easily angered. Cognitively, Yumeaki Iko experiences an identity crisis by choosing to work rather than go to school. In terms of behavior, Yumeaki Iko withdraws from her friends and isolates herself while at school, and behaves naughty by forcing Wako Taira to have sex.